2017
DOI: 10.2527/jas2017.1736
|View full text |Cite
|
Sign up to set email alerts
|

Milk yield and genomewide expression profiling in the mammary gland of beef primiparous cows in response to the dietary management during the pre- and postweaning periods1

Abstract: Accelerated growth programs during prepubertal periods have been promoted to advance the first calving of beef heifers. The objectives of the present study were to evaluate nutrition-induced changes on first lactation milk yield and composition and on gene expression of the mammary gland in Parda de Montaña primiparous cows. Female calves ( = 16) were involved in a 2 × 2 factorial experiment. In the preweaning period (PRE-W; 0-6 mo), female calves were either fed a creep feed supplement (Creep) or fed only the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
1
1
1
Order By: Relevance
“…The lower basal milk yield values with progressing lactation agree with previous data on Parda de Montaña cows (Casasús et al, 2004;Dervishi et al, 2017), and suggest that the peak milk yield had already been reached at the start of the experiment, in month 2, as described by Sapkota et al (2020) for beef cows. In the present study, the reduced milk yield caused by feed restriction falls in line with those reported by other studies of comparable lengths and restriction severities in beef cows (− 12%;De La Torre et al, 2022) and dairy cows (− 13 to − 20% in Abdelatty et al, 2017;Laeger et al, 2012;Nielsen et al, 2003).…”
Section: Cow Performancesupporting
confidence: 89%
See 2 more Smart Citations
“…The lower basal milk yield values with progressing lactation agree with previous data on Parda de Montaña cows (Casasús et al, 2004;Dervishi et al, 2017), and suggest that the peak milk yield had already been reached at the start of the experiment, in month 2, as described by Sapkota et al (2020) for beef cows. In the present study, the reduced milk yield caused by feed restriction falls in line with those reported by other studies of comparable lengths and restriction severities in beef cows (− 12%;De La Torre et al, 2022) and dairy cows (− 13 to − 20% in Abdelatty et al, 2017;Laeger et al, 2012;Nielsen et al, 2003).…”
Section: Cow Performancesupporting
confidence: 89%
“…The negative correlation herein observed between lactose content and somatic cell count has been associated with inflammatory reactions in milk secretory cells (Cinar et al, 2015). However in our study, somatic cell count was always below the threshold for subclinical mastitis (200 × 10 3 cells/mL; Dervishi et al, 2017).…”
Section: Cow Performancecontrasting
confidence: 50%
See 1 more Smart Citation